2013
DOI: 10.1590/s1982-56762013005000016
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization reveals Brazilian Tomato chlorosis virus to be closely related to a Greek isolate

Abstract: Tomato chlorosis virus (ToCV, genus Crinivirus, family Closteroviridae) is a whitefly-transmitted crinivirus with a bipartite RNA genome. This virus is emerging as a serious threat to tomato crops worldwide. To date, only three complete genomic sequences of ToCV have been described from North America, Spain, and Greece isolates. In this study, we present the fourth complete nucleotide sequence of the RNA 1 (8594 nt) and RNA 2 (8242 nt) components of a Brazilian ToCV isolate (ToCV-BR). The complete genome seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
(25 reference statements)
1
10
0
3
Order By: Relevance
“…This disease has rapidly spread across the main tomato production areas in Brazil (Barbosa et al, 2011;Macedo et al, 2014). ToCV is the only crinivirus that has been reported in tomatoes in Brazil (Barbosa et al, 2008(Barbosa et al, , 2011, and little genetic variability has been found among isolates (Albuquerque et al, 2013). Criniviruses belong to the family Closteroviridae, and their genomes are composed of two single-stranded positive-sense RNA molecules.…”
Section: Introductionmentioning
confidence: 99%
“…This disease has rapidly spread across the main tomato production areas in Brazil (Barbosa et al, 2011;Macedo et al, 2014). ToCV is the only crinivirus that has been reported in tomatoes in Brazil (Barbosa et al, 2008(Barbosa et al, , 2011, and little genetic variability has been found among isolates (Albuquerque et al, 2013). Criniviruses belong to the family Closteroviridae, and their genomes are composed of two single-stranded positive-sense RNA molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the accession LA 444‐1 showed a high level of resistance to the begomovirus Tomato yellow vein streak virus (TYVSV) (Matos et al ., ), and the potyvirus Potato virus Y , strain PVY O (Lourenção et al ., ). Taking all these data together and considering the low genetic diversity of the ToCV Brazilian isolates based on the partial nucleotide sequence of the Hsp70h homologous gene (Barbosa et al ., ), as well as the high degree of nucleotide identity with isolates from other countries (Albuquerque et al ., ), it is believed that the lineage IAC‐CN‐RT might be of great value for tomato breeding programmes.…”
Section: Discussionmentioning
confidence: 99%
“…The ToCV isolate used in this study was obtained from a tomato plant in the region of Sumaré, state of São Paulo (Barbosa et al ., ), and the complete genome sequences for both RNAs are deposited in GenBank with accession numbers and (Albuquerque et al ., ). The virus isolate was maintained in tomato plants kept in an insect‐proof cage in the greenhouse.…”
Section: Methodsmentioning
confidence: 97%
“…To date, 17 complete ToCV genome sequences have been published, one each from the USA (Wintermantel et al , ), Spain (Lozano et al , , ), Greece (Kataya et al , ), Brazil (Albuquerque et al , ) and Taiwan (Kang et al , ), two from China (Zhao et al , , 2014b) and ten from Korea (Lee et al , ).…”
Section: Genome Organization and Diversitymentioning
confidence: 99%